Multidisciplinary design analysis and optimization of aerospace composite materials - Lu, Y. Charles (SAE International, 2020)
A collection of ten SAE technical papers focusing on the design analysis of aerospace composite structures from the perspective of various disciplines.
Keywords: Aerospace engineering.; Composite materials.; elektronické knihy; electronic books